A Review of Sampling Techniques in Social Science Research - Rawat, Anviti (AG Volumes, 2025)
The sampling procedure has a significant impact on a study’s accuracy. Because they have the power to determine the validity of results, choosing the right sample size and selection procedure for a given research problem is essential. Examine the many studies on sampling methods in social science research that have been published in the literature. This review highlights the critical role of sampling techniques in social science research, emphasizing the trade-offs between probability and non-probability methods. While probability sampling ensures representativeness and statistical reliability, non-probability sampling offers practical advantages in terms of cost, speed, and feasibility, especially in digital research contexts like Twitter. However, limitations such as lack of generalizability and inability to compute confidence intervals must be acknowledged. Ultimately, the choice of sampling technique should align with the research objectives, available resources, and population characteristics to ensure valid, reliable, and meaningful findings in social science inquiry.